Who, Where, What, Wren? Using Ancient DNA to Examine the Veracity of Museum Specimen Data: A Case Study of the New Zealand Rock Wren (Xenicus gilviventris) - Verry, Alexander J. F.; Scarsbrook, Lachie; Scofield, R. Paul; Tennyson, Alan J. D.; Weston, Kerry A.; Robertson, Bruce C.; Rawlence, Nicolas J. (Frontiers in Ecology and Evolution, 2019)
Museum specimens provide a record of past species distribution and are an increasingly important resource for conservation genetic research. The scientific value of these specimens depends upon the veracity of their associated data and can be compromised by inaccurate details; including taxonomic identity, collection locality, and collector. New Zealand contains many endemic species that have been driven to extinction or reduced to relict distributions following the arrival of humans and mammalian predators, including the Acanthisittid wrens (of which only two of the eight species presently persist). One of these is the New Zealand rock wren (Xenicus gilviventris), currently classified as an endangered species and experiencing ongoing population declines. Here we analyse ancient DNA retrieved from New Zealand rock wren museum skins to establish the veracity of their recorded collection localities – New Zealand rock wrens exhibit strong north-south genetic structuring along the Southern Alps of New Zealand’s South Island. We include the only specimen reportedly collected from New Zealand’s North Island, outside the known range of New Zealand rock wrens, specimens collected by Henry Hamersley Travers, a collector known for poor record keeping and potentially fraudulent specimen data, and type specimens of proposed Xenicus taxa. Multiple instances of inaccurate collection locality were detected, including that of the New Zealand rock wren reportedly collected from the North Island, which matches individuals from the southern South Island. Syntypes of X. haasti, and a syntype of X. gilviventris clustered with individuals belonging to the northern New Zealand rock wren lineage. Our results suggest that New Zealand rock wrens have not been historically extirpated from New Zealand’s North Island, and that caution must be taken when utilising museum specimens to inform conservation management decisions. Additionally, we describe the type locality of both X. gilviventris and X. haasti, with genetic and historical evidence suggesting that the specimens used to describe these taxa were collected from the headwaters of the Rakaia River. This study demonstrates that ancient DNA analysis can add value to museum specimens by revealing incorrect specimen data and inform the conservation management and taxonomy of endangered species.